Culture, Actors, and Resources Surrounding Undergraduate Bioethics Education in Sub-Saharan Africa - Bruce, Elizabeth R. (International Journal of African Higher Education, 2019)
Scientisation is a growing trend as individuals worldwide harness scientific tools and knowledge to solve problems. This phenomenon is evident in biomedical research, which has increased across sub-Saharan Africa, and when encountering bioethical issues arising during the course of such research. This research synthesis considers how the constructs of culture, actors, and resources in the region shape undergraduate bioethics education. Using a lens of sociological neo-institutionalism, taken-for-granted bioethical scripts, like informed consent and medical confidentiality, are evident in this education; however, actual implementation demonstrates the way they are often adapted and contextualized with implications for students and instructors, and ultimately patients and research participants. The education considered is that for undergraduates in health sciences and medicine because they are prominent actors in research and clinical practice across the region. In considering insights from this literature, the aim is to positively impact health across sub-Saharan Africa. Le phénomène de scientifisation est de plus en plus répandu : partout dans le monde, les individus s’emparent des outils et connaissances scientifiques pour résoudre des problèmes. C’est particulièrement visible dans le domaine de la recherche biomédicale, qui se développe dans toute l’Afrique subsaharienne, et lorsqu’on considère les questions bioéthiques qui se posent au cours desdites recherches. La présente recherche explore la façon dont les concepts de culture, d’acteurs et de ressources dans la région influencent l’enseignement de la bioéthique durant le premier cycle universitaire. A travers le prisme d’un néo-institutionnalisme sociologique, on constate que les écrits fondateurs de la bioéthique, tels que le consentement éclairé et le secret médical, sont des composantes évidentes de cet enseignement. Cependant, leur mise en oeuvre sur le terrain révèle que ces principes sont souvent adaptés et contextualisés, ce qui a des conséquences pour les étudiants, les formateurs et à terme les patients et les personnes qui participent aux recherches. Cet article se concentre sur l’enseignement du premier cycle universitaire dans les domaines des sciences de la santé et de la médecine, qui sont des acteurs incontournables de la recherche et de la pratique clinique dans la région. En prenant en compte les apports de la littérature, l’objet de cette recherche est d’avoir un impact positif sur le secteur de la santé en Afrique subsaharienne.